THE EFFECT OF GUIDED INQUIRY LEARNING IMPLEMENTATION ON STUDENTS’ LEARNING OUTCOMES IN TEMPERATURE, HEAT AND EXPANDING MATRIALS - EfiT, Debby Tria Oktanesa; Zahra, Firda Az (Department of Science Education, 2024)
This research is motivated by the results of observations of 7th grade students at SMPN 29 Padang for the 2021/2022 academic year. It is known that there are still many students who in the learning process are less active and cooperate with each other. Student learning outcomes are classified as low with an average below the Minimum Completeness Criteria (KKM) of 80. Teacher apply teacher centered learning methods in the learning process. This study aims to determine the increase in student learning outcomes with the Guided Inquiry learning model on the material Temperature, heat and expansion. This research was conducted at SMPN 29 Padang for the 2022/2023 school year. The samples in this study were 32 students of class VII.6 and 32 students of class VII.7. This type of research is quasi-experimental research with a non-equivalent control group design. The sampling technique used was purposive sampling. The research instrument used a test instrument in the form of an objective test of 30 questions. Data analysis used the normality test, homogeneity test and parametric test, namely the t test to see an increase in student learning outcomes. The results showed that there was an increase between before and after the application of the Guided Inquiry learning model where t count was greater than t table, namely 7.62 > 1.67.